The role of effective communication as the key to family resilience in families with young children during times of crisis - Azhar, Aghnia Farrassyania; Musfita , Regita; Nurcahyani, Ratna Dwi; Rizkita, Diantifani (Tunas Siliwangi, 2024)
In contemporary times, research on family resilience is crucial. This is because every family faces unique challenges and is required to adapt, cope with, and recover from various difficulties and obstacles. These challenges may include economic issues, health problems, technological advancements, social changes, and other various problems. Gradually, these issues can weaken the family's function in shaping character and facilitating child development. The objective of this case study is to examine how the communication process serves as a key factor in building family resilience among families with young children. This qualitative research employed a case study approach with three families with young children as subjects. Data was collected through interviews and observations, and analyzed using thematic analysis. The results indicate the presence of components of the communication process as a key to family resilience in the three participating families. All three participating families have established guidelines for communication, avoiding ambiguity, maintaining positive interactions, and having guidelines for resolving existing problems.